Survey on the current practice of research ethics committees in the Czech academic environment: a mixed-methods study - Veselska, Renata; Sirucek, Jan; Kure, Josef (BMC medical ethics, 2024)
The primary objective of this study was to conduct a comprehensive questionnaire survey on the practices of research ethics committees reviewing academic research projects in Czechia. The study aims to provide an unbiased and objective assessment of the current practices of research ethics committees, namely to obtain the missing data on their functioning in the context of academic research, to identify difficulties and shortages that threaten the responsible functioning of research ethics committees in the country and to investigate the implementation of Additional Protocol on Biomedical Research CETS No. 195 in their practice. Such research has never been conducted in Czechia. This was a mixed-methods study, in which the online survey with closed and open-ended questions was chosen to explore the situation regarding ethics assessment of research involving human participants. We developed a questionnaire containing 18 questions concerning several aspects of the functioning of research ethics committees. The questionnaire was in Czech language and was administered through the Qualtrics platform anonymously. The target group of 61 research ethics committees at research institutions was approached by emails and we received 43 completely filled questionnaires, i.e., response rate of 67%. We obtained valuable data on the functioning of research ethics committees in Czechia in three main domains: the mandate and composition of the committee; the scope of its agenda; the process of evaluation including the voting procedure. In addition, the final set of open-ended questions provided an in-depth look at the problems faced by research ethics committees in Czechia. From the results is evident that the responsible assessment of the ethics of research involving human subjects is still not satisfactorily addressed and established for routine practice in the country. The outcomes of our study revealed that the main problem of research ethics in Czechia is the lack of national legislation on research ethics governance. To address this problem, the country requires a legislative framework accompanied by supportive measures aimed at educating, guiding and advising research ethics committees, especially in the Czech academic environment. Not applicable.